Training needs analysis for sustainable practices among FPA students / Muhammad Faez Mohd Rosli - Mohd Rosli, Muhammad Faez (2019)
Training Needs Analysis (TNA) is an alternative method of identifying the gap between the undergo training and needs of training. Training Need Analysis is the first thing to do in the training process and continuously develop a series of stage that will prove either the training can solve the problem which has been recognized or not. In this study, researcher decided to analyze the needs for several training about sustainable practices of agriculture in Malaysia among agriculture students. The objective of this study is to identify the undergo knowledge of FPA students toward sustainable practices in Malaysia. The study was conducted in UiTM Jasin, Malacca. The population size of this study is about 728 students consist of 522 students of diploma and 206 students of degree. So based on Raosoft sample size calculator, the ideal sample size suggested were 222 diploma‟s students and 135 degree‟s students. The method of this research is by simple random sampling. All of the data were collected through distribution of questionnaires to the respondents and analyze it by using SPSS software. Through the survey that has been carried out, the higher correlation among independent variables is GAP (0.529). While the dominant factors that influence the training needs are GAP, OSHA, and chemical usage practices. Finding of this study had shown that student‟s analysis towards the independent variables for this research (R2) is 66.7% and the rest 33.3% were not included in this research. The finding from this research can help undergraduate to prepare themselves before graduating. Usually most of students still not ready to be in the industry as they are lack of exposure namely in term of knowledge and type of training that has been implemented in Malaysia. Thus, this research can give a guideline for students and prevent them from giving up their dreams to work in plantation sector.